(untitled) (Tempo e Argumento, 2021)
This article reflects on religions and religiosities as issues concerning historical studies based on concepts and categories belonging to the History of the Present Time. To do this, it starts from the verification of the presence of religion in our present time and the expansion of this presence, particularly in the contemporary political field. It presents, as an introduction, a brief overview of the studies on religions and religiosities, highlighting etymological and epistemological elements that delimit the field at stake. Also, it discusses the place of memory in the frame of religions – more specifically, in Christian denominations – based on the analytical tools proposed by Danièle Hervieu-Léger. And, finally, it addresses the reflection on memory through a brief analysis of data regarding religious conversion in Brazil, also referring to Christian denominations, during the last 20 years. Keywords: religion; memory; history of the present time